Knowledge management: Preserving, managing and sharing indigenous knowledge through digital library - Tsetselelane D. Mdhluli (AOSIS, 2021)
Indigenous peoples’ ways of preserving, managing and sharing knowledge are argued to have contributed to their knowledge being threatened with extinction. This article addresses the need for intergenerational transmission of culturally unique knowledge for future generations through digital libraries. The speedy use of digital media in the modern, dynamic world gives valuable opportunities to facilitate the process of preserving, managing and sharing knowledge that are unique to South African communities. The use of qualitative research ensured a deep inquiry and understanding of digitalising indigenous knowledge. The modernisation theory was grounded by African indigenous ways in designing the framework. This article proposes the use of digital libraries in knowledge management so as to reach a wider audience. More so, digitalisation should be premised to ensure that the knowledge is protected against intellectual theft and allow knowledge holders and communities to benefit from such initiatives.